2022
DOI: 10.1002/dvdy.549
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Galectin 3 binding protein is the target antigen of the microglial 4C4 monoclonal antibody

Abstract: Background:Two decades ago, the fish-specific monoclonal antibody 4C4 was found to be highly reactive to zebrafish microglia, the macrophages of the central nervous system. This has resulted in 4C4 being widely used, in combination with available fluorescent transgenic reporters to identify and isolate microglia. However, the target protein of 4C4 remains unidentified, which represents a major caveat. In addition, whether the 4C4 expression pattern is strictly restricted to microglial cells in zebrafish has ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…N=21 animals, p=0.0397 3 dpf vs 5 dpf, Post hoc Tukey Test). We confirmed this debris was derived from microglia and not from other pu1 + macrophages that may enter the embryonic brain by demonstrating they also label with the zebrafish microglia-specific antibody 4C4 (Figure 1c) 13,14 . To investigate how this debris could occur, we generated movies of Tg(pu1:gfp) animals for 24 hours (Movie S1).…”
Section: Main Textmentioning
confidence: 55%
“…N=21 animals, p=0.0397 3 dpf vs 5 dpf, Post hoc Tukey Test). We confirmed this debris was derived from microglia and not from other pu1 + macrophages that may enter the embryonic brain by demonstrating they also label with the zebrafish microglia-specific antibody 4C4 (Figure 1c) 13,14 . To investigate how this debris could occur, we generated movies of Tg(pu1:gfp) animals for 24 hours (Movie S1).…”
Section: Main Textmentioning
confidence: 55%
“…Since resident and infiltrating immune cells can be detected after retinal damage, we sought to determine if senolytic treatment impacted the overall number of 4c4 + immune cells in the retina. The 4c4 antibody targets the galectin 3 antigen in zebrafish microglia 66 . All three senolytic treatments showed little to no change in 4c4 + cells in the retina ( Figure S1–3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used a macrophage reporter line that expresses green fluorescent protein (GFP) under the macrophage expressed gene 1 promoter, mpeg1 : GFP , and 4C4 immunostaining to label microglia (GFP+, 4C4+) and macrophages (GFP+, 4C4−) after injury. The 4C4 antibody binds to a paralog of the Galectin 3 binding protein (Lgals3bpb) expressed selectively by microglia in the adult zebrafish brain (Rovira et al, 2022). We found that macrophages began to accumulate 2 hours post lesion (hpl), the increase in macrophages peaked at 1 day post lesion (dpl) and then macrophage numbers declined sharply at 2 dpl but remained significantly elevated compared to the control through 4 dpl (Figure 1c,d and Figure S1a).…”
Section: Resultsmentioning
confidence: 99%